Controls of alluvial cover formation, morphology and bedload transport in a sinuous channel with a non‐alluvial boundary. Issue 2 (29th November 2020) - Papangelakis, E.; Welber, M.; Ashmore, P.; MacVicar, B.
Abstract: The alluvial cover in channels with non‐alluvial beds is a major morphologic feature in these rivers and has important geomorphic and ecologic functions. Although controls on the extent of the alluvial cover have been previously researched, little is known about the role of channel meanders in shaping the three‐dimensional morphology and bedload transport rates in these rivers. Flume experiments were conducted in a fixed‐bed sinuous channel scaled from an engineered urban river. A fully graded sediment supply mixture was fed into the bare channel at rates ranging between 0.3 and 1.2 times the estimated channel capacity under constant discharge. The three‐dimensional morphology and surface texture of the alluvial cover were captured using photogrammetry, and the sediment output was periodically measured and sieved. A stable alluvial cover was achieved under all sediment supply conditions that coincided with a sediment transport equilibrium. The sediment supply rate controlled the final areal extent, mass and volume of the alluvial cover, while cover developed as a periodic series of stable bars 'fixed' by the channel planform. The alluvial cover development followed consistent trajectories relative to angular position around bends but developed to a greater degree and higher elevation with increasing sediment supply. The stable cover extent had a logarithmic relationship with the relative sediment supply, while the final mass, volume and bar height had linear relationships. The final channel morphology was characterized by fine‐textured point bars with flat tops and steep margins connected by coarse riffle features. The outside of banks between bend apexes remained bare, even at sediment supply conditions exceeding the channel capacity. The length of the exposed outer banks followed predictable linear relationships with the total cover extent. Insights from this study can provide guidance for the management of channels with non‐alluvial boundaries and provide validation for models of sinuous bedrock channel abrasion. © 2020 John Wiley & Sons, Ltd. Abstract : Physical experiments were conducted in a scaled model of a sinuous channel with a non‐alluvial bed to monitor the dynamics of the alluvial cover under varying sediment supply conditions. Sediment supply rate and planform geometry had interacting but distinct controls on the formation, three‐dimensional morphology and surface texture of the alluvial cover. The bedload transport capacity of the channel adjusted through cover development to equilibrate with the sediment supply rate under all experimental conditions.